Phytoremediation of soil contaminated with used lubricating oil using Jatropha curcas - Agamuthu, Pariatamby; Abioye, O.P.; Abdul Raman, Abdul Aziz (Elsevier, 2010)
Soil contamination by used lubricating oil from automobiles is a growing concern in many countries, especially in Asian and African continents. Phytoremediation of this polluted soil with non-edible plant like Jatropha curcas offers an environmental friendly and cost-effective method for remediating the polluted soil. In this study, phytoremediation of soil contaminated with 2.5 and 1 (w/w) waste lubricating oil using curcas and enhancement with organic wastes Banana skin (BS), brewery spent grain (BSG) and spent mushroom compost (SMC) was undertaken for a period of 180 days under room condition. 56.6% and 67.3% loss of waste lubricating oil was recorded in Jatropha remediated soil without organic amendment for 2.5% and 1% contamination, respectively. However addition of organic waste (BSC) to Jatropha remediation rapidly increases the removal of waste lubricating oil to 89.6% and 96.6% in soil contaminated with 2.5% and 1% oil, respectively. Jatropha root did not accumulate hydrocarbons from the soil, but the number of hydrocarbon utilizing bacteria was high in the rhizosphere of the Jatropha plant, thus suggesting that the mechanism of the oil degradation was via rhizodegradation. These studies have proven that J. curcas with organic amendment has a potential in reclaiming hydrocarbon-contaminated soil. (C) 2010 Elsevier B.V. All rights reserved.